Urdu Historical Novels in the Colonial Era and Contemporary Awareness - Abbas Kazmi, Kamran; Nawaz, Tahir (sourcecoder, 2022)
Novel is the most popular genere of Urdu fiction. The Novel expresses human life. It depicts nature as well as depicts human habits, customs and the realities of life. History has been an important subject of Urdu novels. History tells the story of human social and cultural evolution while the novel reflects social, cultural, civilizational and political life. It is as if the novel not only reflects the society of the past but also preserves it. Urdu historical novels and contemporary awareness discussed in this article